IDENTIFIKASI PENDAPATAN ASLI DAERAH (PAD) KABUPATEN KEPULAUAN SANGIHE MENUJU PEMEKARAN WILAYAH - Radangkilat, Reyne Ivone; RARES, Joyce J; Kiyai, Burhanuddin (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACTThis study describes how the contribution of the Locally-Generated Revenue (LGR) sources ofSangihe Islands Regency to the total LGR and the effectiveness level of the acceptance of the LGR sourcesin Sangihe Islands Regency.The method used in this research is descriptive qualitative method with secondary data obtained fromthe Department of Financial Revenue Management and Local Asset of Sangihe Islands Regency. Datacollection techniques are documentation study and literature study with contribution analysis techniquesand level of effectiveness.The results of data analysis show that the average value of the contribution of the revenue sources(Local Taxes, Local Levies, Local Resources Management, and Miscellaneous Legal Revenue) of SangiheIslands Regency in the fiscal year of 2009-2013 was respectively 11.73 %, 50.93 %, 5.36 %, and 31.92 %;and the average value of the effectiveness level of the LGR acceptance of Sangihe Islands Regency in thefiscal year of 2009-2013 was 89.26%, or already effective.Based on the results of this study, it can be concluded that the Local Levies sources provide thelargest contribution to the total LGR in the fiscal year of 2009-2013, followed by Miscellaneous LegalRevenue, Local Taxes, and Separated Local Resources Management. In terms of the level of effectiveness,the administration of revenue sources of LGR in the fiscal year of 2009-2013 has been effective. However,there are several factors inhibiting the increase in the LGR of Sangihe Islands Regency; among others,human resources (HR), supervision, and coordination.This study then suggests that the LGR of Sangihe Talaud be increased, the performance of SKPDneeds to be optimized to generate LGR, and some of the factors inhibiting the increase in LGR needsserious attention from the government.Key word : Locally-Generated Revenue (LGR), Regional Divisions